Analisis Sistem Proteksi Penangkal Petir Eksternal Dengan Metode Sudut Pada Gedung Bertingkat - Nurhabibah Naibaho; Aditya Farhanuddin (Teknik Elektro Universtias Krisnadwipayana, 2026)
Geographically Indonesia as a tropical country located on the equator and is a maritime continent with a vast sea, relatively high rainfall causes relatively high air humidity, this causes lightning clouds containing electric charges to form very easily with destructive properties, seeing some of the damage that usually arises due to lightning strikes, then an effort to overcome the strike is known as lightning protection. In this type of research, a type of quantitative research is carried out with the processing and calculation of output data from observations including multi-storey building data, thunder days, specifications and types of lightning rods, lightning current conductors, and grounding systems with standard criteria based on the 1983 General Lightning Installation Regulations (PUIPP) and SNI 03-7015-2004. estimated risk of lightning strikes index value of 22, average annual strike frequency of 2.43 strikes and lightning strike efficiency value of 0.96 protection level I. minimum cross-sectional area 22.5 mm. Minimum cross-sectional area of 22.5 mm2, 2x35 mm2 coaxial cable installed and the total resistance value of multiple ground rod electrodes of 1.04Ω, a maximum of 2.5Ω is in accordance with the standard and in the air termination with the calculation of the radius of the rolling ball with a radius of 20 m lightning strikes each end of the building side are still exposed to the touch of the rolling ball. Because the air termination installed is conventional type, the calculation of air termination with electrostatic lightning rod protection Angle a is ∠42.06º with a lightning strike distance to the building as high as 134.15 m. Therefore, optimization is carried out using an electrostatic type lightning rod Flash Vectron FV6 brand with a radius of 140 m.